Resolução CSMPF nº 48, de 2 de março de 1999 - Haroldo Ferraz da Nobrega; Paulo de Tarso Braz Lucas; Henrique Fagundes Filho; Roberto Monteiro Gurgel Santos; Wagner Mathias; Wagner Goncalves; Helenita Amelia Caiado Goncalves de Acioli; Wallace de Oliveira Bastos; Sandra Veronica Cureau (DJ, Brasília, DF, p. 191, 12 mar. 1999., 1999)
Altera o art. 3º, inciso II, da Resolução CSMPF nº 33, de 17 de dezembro de 1997.